Yield reduction due to loss in soil fertility through erosion - Mokhtaruddin, A. M.; Jamal, T.; Wan Sulaiman, W. H.; Anuar, A. R. (1984)
In this paper yield of maize (Zea may) planted on 8 to 10% slope was compared to that planted on flat land of the same soil and locality with same fertilizer rate,the yields of maize planted on slope with and without tillage were 41 and 35% of that grown on flat land. The total soil loss during the growing period were 145 and 70kg.ha-1. When the sloping land was left bare for eight months ansd then planted with maize,the yield was only 5% of that of the flat land. The total,soil loss during the 8 month pre0planting period was 26 tonnes/Ra. The results clearly demonstrated that erosion leads to the removal of the more fertile topsoil and considerable loss of fertilizer. The loss in the fertility is often the major limitation in crop productivity when sloping land is put under cultivation.